Associations Between Maternal Pre- and Postnatal Depressive Symptoms and Brain Electrophysiology in 3-year-olds - Laihonen, Emilia (My University, 2025)
Maternal pre- and postnatal depressive symptoms are common in women, which has led to a widespread interest in developmental neuroscience with the key question of, whether maternal depressive symptoms associate with child brain development. Electroencephalography (EEG) signals capture both periodic and aperiodic activity and aperiodic parameters (offset and exponent) both of which have been shown to have a tight connection to early brain development. Despite some prior studies implicating an association between maternal perinatal distress and offspring´s brain electrophysiology, the relationship between maternal perinatal depressive symptoms and the aperiodic activity of EEG remains unstudied. This study builds on the data collected as part of the FinnBrain Birth Cohort study, and investigated the associations between aperiodic parameters (offset and exponent) of the EEG power spectrum in 3-year-olds (N = 56) and maternal pre- and postnatal depressive symptoms (assessed with the Edinburgh Postnatal Depression Scale) that were collected at gestation week 24 and at 3, 6 and 12 months postpartum. Data consisted of 28 boys and 28 girls and the mean age during the EEG recording was 1115 days (SD = 30.8). EEG power spectrum was parameterized to aperiodic and periodic components using the SpecParam software. Postnatal age of the child, sex of the child and gestational duration were included as covariates. Our results showed that maternal postnatal depressive symptoms (at 6 months postpartum) had a statistically significant negative association with the offspring’s aperiodic offset (β = 0.23, p = 0.026), indicating a uniform negative shift in the power of the spectrum as postnatal maternal depressive symptoms increase. In addition to that, we found nearly statistically significant negative association between prenatal maternal depressive symptoms (at gestational week 24) and the offspring’s offset (β = -0.16, p = 0.051). In conclusion, our results suggest that maternal perinatal depressive symptoms may affect offspring’s brain electrophysiology. Future studies are needed to explore the role of aperiodic activity changes as a possible mediator for the effects of maternal perinatal distress on the child’s developmental outcomes.

Äidin perinataalinen (raskaudenaikainen ja synnytyksen jälkeinen) masennusoireilu on yleistä, ja sen on osoitettu voivan lisätä lapsen riskiä sairastua erilaisiin käytös- ja mielenterveyden häiriöihin. Elektroenkefalografia (EEG) mittaa sekä jaksottaista eli periodista että jaksotonta eli aperiodista aivojen aktiivisuutta. Aperiodisen aktiivisuuden on osoitettu aikaisemmissa tutkimuksissa muuttuvan iän myötä. Vaikka aikaisemmissa tutkimuksissa on osoitettu yhteys äidin perinataalisen stressin ja lapsen aivojen sähköisen toiminnan välillä, äidin masennusoireiden ja lapsen EEG:n aperiodisen aktiivisuuden välistä suhdetta ei ole juuri tutkittu. Tämä poikittaistutkimus perustuu FinnBrain-syntymäkohorttitutkimuksen aineistoon. Tutkimuksessa selvitettiin EEG:n tehospektrin aperiodisten muuttujien (offset ja eksponentti) yhteyttä äidin perinataalisiin masennusoireisiin 3-vuotiailla lapsilla (N = 56, joista 28 tyttöä). Lasten keskimääräinen ikä oli 1115 päivää (keskihajonta = 30,8). Äidin masennusoireilua kartoitettiin Edinburghin synnytyksenjälkeisen masennuksen seulontalomakkeella (EPDS) raskausviikolla 24 sekä 3, 6 ja 12 kuukautta synnytyksen jälkeen. Aivosähkökäyrästä laskettiin ensin kullekin lapselle tehospektri, joka kuvaa signaalin tehon jakautumista eri taajuuksille. Tehospektri jaettiin edelleen periodiseen ja aperiodiseen osaan Specparam-menetelmällä. Lapsen syntymästä laskettu ikä, sukupuoli ja raskauden kesto kontrolloitiin tilastomalleissa. Tuloksemme osoittivat äidin synnytyksen jälkeisten masennusoireiden (6 kuukautta synnytyksen jälkeen) ja lapsen offset-arvojen (β = -0,23; p = 0,026) välillä tilastollisesti merkitsevän negatiivisen yhteyden, mikä tarkoittaa matalampaa EEG-spektrin tehotasoa (eli tasoa, jolle spektri asettuu) niillä lapsilla, joiden äidin masennusoireilu oli korkeampaa. Lisäksi havaitsimme lähes tilastollisesti merkitsevän negatiivisen yhteyden äidin raskaudenaikaisten masennusoireiden (raskausviikolla 24) ja lapsen offset-arvojen välillä (β = -0,16; p = 0,051). Tuloksemme viittaavat siihen, että äidin perinataaliset masennusoireet voivat vaikuttaa lapsen aivojen sähköiseen toimintaan. Jatkossa olisi hyvä tutkia sitä, voivatko EEG:n aperiodisessa aktiivisuudessa todetut muutokset osaltaan selittää äidin perinataalisen stressin yhteyttä lapsen myöhempään kehityksellisten häiriöiden riskiin.
Keywords: maternal depressive symptoms, brain, electroencephalography, EEG, brain electrophysiology, aperiodic activity, children